4(3z+2)=-13z-10

Simple and best practice solution for 4(3z+2)=-13z-10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(3z+2)=-13z-10 equation:


Simplifying
4(3z + 2) = -13z + -10

Reorder the terms:
4(2 + 3z) = -13z + -10
(2 * 4 + 3z * 4) = -13z + -10
(8 + 12z) = -13z + -10

Reorder the terms:
8 + 12z = -10 + -13z

Solving
8 + 12z = -10 + -13z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '13z' to each side of the equation.
8 + 12z + 13z = -10 + -13z + 13z

Combine like terms: 12z + 13z = 25z
8 + 25z = -10 + -13z + 13z

Combine like terms: -13z + 13z = 0
8 + 25z = -10 + 0
8 + 25z = -10

Add '-8' to each side of the equation.
8 + -8 + 25z = -10 + -8

Combine like terms: 8 + -8 = 0
0 + 25z = -10 + -8
25z = -10 + -8

Combine like terms: -10 + -8 = -18
25z = -18

Divide each side by '25'.
z = -0.72

Simplifying
z = -0.72

See similar equations:

| 10x+5x-7+3=0 | | 6+2y=12x | | 2x-2=2x+5 | | 7-z/5=0.25 | | z-2000=0.375 | | 20=(1/4)a | | X^6-15=0 | | 1x-5(-2)=15 | | (z-2000)/5000=0.375 | | z-2000/5000=0.375 | | (m-n)-(6m+7n)= | | (5x-7y)-(5x+7y)= | | 3(2)+2(-3)= | | (6x)^(5/2)-(3x)^(3/2) | | 3x^2-36x=-80 | | -3(x-1)-2x=4(x+4)+4 | | (5x-7y)-(5x-7y)= | | 4x^2+8x+80=6x^2-4x | | 7-4x=8x+5 | | x*3-7x+4=0 | | 0.09x^2-30x+600=0 | | 100+5+5x=180 | | 15-m=24 | | 3x+42+90=180 | | (2.5-z)/(2.5-1)=0.06 | | (x+y)+(x+y)+(x+y)= | | (10+11*-1)+3(4*-1+3)= | | (10+11*-1)+3(4*-1+3)=2 | | -4.6y-2(2.2y-7.2)=-2.1(y-20) | | 5y-1-3y=5.20 | | 7y(2x-5y)= | | (7a+7b)+(6a-8b)= |

Equations solver categories